1980
DOI: 10.1093/ajcn/33.8.1869
|View full text |Cite
|
Sign up to set email alerts
|

Influence of type of carbohydrate on atherosclerosis in baboons fed semipurified diets plus 0.1% cholesterol

Abstract: Five groups of six (three male, three female) baboons (Papio ursinus) were maintained for 17 months on a semipurified diet containing 40% carbohydrate, 25% casein, 13.9% coconut oil, 0.1% cholesterol, 15% cellulose, 5% salt mix (USP XIV) and 1% vitamin mix. The carbohydrates fed were: fructose, sucrose, starch, glucose, and lactose. A fifth group was used as control and was fed bread, fruit, and vegetables. Serum, liver, and tissue lipids were analyzed at the end of the feeding period as were cholesterol absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…The sucrose-induced increase in TG-rich lipoprotein and increased lipoprotein susceptibility to peroxidation are factors that may combine to increase risk of cardiovascular diseases (29). Compared with starch feeding, sucrose feeding thus results in a higher occurrence of aortic atherosclerotic plaque in animal models as previously reported (30). Moreover, we found that heart tissue from male sucrose-fed rats was more susceptible to in vitro peroxidation than that from the starch group.…”
Section: Discussionsupporting
confidence: 84%
“…The sucrose-induced increase in TG-rich lipoprotein and increased lipoprotein susceptibility to peroxidation are factors that may combine to increase risk of cardiovascular diseases (29). Compared with starch feeding, sucrose feeding thus results in a higher occurrence of aortic atherosclerotic plaque in animal models as previously reported (30). Moreover, we found that heart tissue from male sucrose-fed rats was more susceptible to in vitro peroxidation than that from the starch group.…”
Section: Discussionsupporting
confidence: 84%
“…An increase in the TG-rich lipoprotein levels and in the lipoproteins' susceptibility to peroxidation are factors that may contribute to an increased risk of developing cardiovascular diseases. Compared with the potato-based diet, sucrose consumption resulted in a higher frequency of aortic atherosclerotic plaques in animal models, consistent with previous reports [43].…”
Section: Health Effects Of Potatosupporting
confidence: 92%
“…Earlier Wells and Anderson [11] found lactose to be hypercholesterolemic in rabbits, but these findings were not substantiated by Kritchevsky et al [12], Kritchevsky et al [13] did, however, observe an increased incidence o f atheroscle rosis in baboons fed 0.1 % cholesterol in a 40% lactose diet as compared to fructose, glucose, sucrose or starch.…”
mentioning
confidence: 89%